Step-by-step explanation
Given the Newton’s Law of universal Gravitation:
![F=G(m_1\cdot m_2)/(r^2)](https://img.qammunity.org/2023/formulas/mathematics/college/u385c6t2qopyqug2udpd800q4jwrbl0c6c.png)
As the force is of 36 N, we can substitute It on the function:
![F=G(m_1\cdot m_2)/(r^2)](https://img.qammunity.org/2023/formulas/mathematics/college/u385c6t2qopyqug2udpd800q4jwrbl0c6c.png)
If the mass of both objects is doubled, then the force will be stronger by a factor of 4:
![F=G(2m_1\cdot2m_2)/(r^2)=G(4m_1m_2)/(r^2)](https://img.qammunity.org/2023/formulas/mathematics/college/m7vojzoms45p0ym5otsa2zhr1lavg7at5h.png)
Also, if the distance between them is doubled, then we will get a factor of 4 as shown as follows:
![F=G(2m_1\cdot2m_2)/((2r)^2)=G(4m_1m_2)/(4r^2)](https://img.qammunity.org/2023/formulas/mathematics/college/sar6shl6y0emly813poe2koi4uamhcnru9.png)
Then, simplifying both numbers 4, we can conclude that the force will be the same:
![F=G(2m_1\cdot2m_2)/((2r)^2)=G(4m_1m_2)/(4r^2)=G(m_1m_2)/(r^2)\text{ \lbrack{}Same expression\rbrack}](https://img.qammunity.org/2023/formulas/mathematics/college/4dawrp4d3k9jl7zfq5npuq6jhjwwigcxbr.png)